2010
DOI: 10.1007/s10388-010-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Registry of Esophageal Cancer in Japan, 2002

Abstract: 276 institutions in Japan. Tumor locations were cervical: 4.4 %, upper thoracic: 11.9 %, middle thoracic: 48.0 %, lower thoracic: 27.7 % and EG junction: 6.6 %. Superficial carcinomas (Tis, T1a, T1b) were 36.7 %. As for the histologic type of biopsy specimens, squamous cell carcinoma and adenocarcinoma accounted for 90.5 and 3.8 %, respectively. Regarding clinical results, the 5-year survival rates of patients treated using endoscopic mucosal resection, concurrent chemoradiotherapy, radiotherapy alone, chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Although adenocarcinoma is the most prevalent subtype (>50%) of esophageal cancer in the USA (9), >90% of esophageal cancer cases are ESCC in Japan (10,11). Thus, in the present study we investigated whether Girdin is also involved in the motility of ESCC cells.…”
Section: Introductionmentioning
confidence: 97%
“…Although adenocarcinoma is the most prevalent subtype (>50%) of esophageal cancer in the USA (9), >90% of esophageal cancer cases are ESCC in Japan (10,11). Thus, in the present study we investigated whether Girdin is also involved in the motility of ESCC cells.…”
Section: Introductionmentioning
confidence: 97%
“…A nationwide registry of 5066 Japanese patients with esophageal cancer treated in 2004 showed that second cancers in another organ were present in 981 patients (19.4%). Gastric cancer was the most common form of cancer (353 lesions), followed by H&N cancer, including 162 pharyngeal cancers, 66 laryngeal cancers and 24 cancers in the oral cavity (17). We previously reported that both heavy smoking and heavy drinking are well-established risk factors for HNC and ESCC, and for multiple occurrences of cancer in these areas (2,18,19); the current study revealed the synchronous combination of superficial ESCC and advanced HNC are most frequently recognized.…”
Section: Discussionmentioning
confidence: 93%
“…, Naohiko Koide 1) , Akira Suzuki 1) , Daisuke Takeuchi Department of Clinical Laboratory Medicine, Shinshu University Hospital A 64 year-old woman complained of dysphagia. Esophagogastroduodenoscopy showed an elevated tumor (type-1) in the middle thoracic esophagus, and biopsy specimens taken from the tumor histopathologically revealed neuroendocrine carcinoma and carcinosarcoma.…”
Section: .本例では,術後の病理組織学的検査所見では病変のmentioning
confidence: 99%